2011
DOI: 10.1515/hf.2011.148
|View full text |Cite
|
Sign up to set email alerts
|

Natural and artificial ageing of spruce wood as observed by FTIR-ATR and UVRR spectroscopy

Abstract: Spruce samples, naturally aged for 200, 400 and 500 years, artificially aged by a hydrothermal treatment (at 180, 160 or 1308C, relative air humidities of 14%, 40%, or 60% and for treatment times between 1 to 50 h), as well as reference samples, were analysed by Fourier transform infrared spectroscopy (FTIR) attenuated total reflection (FTIR-ATR) and ultraviolet resonance Raman (UVRR) spectroscopy. Natural ageing mostly affected the hemicelluloses and lignin, as observed from the FTIR-ATR and UVRR spectra, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 32 publications
2
40
0
2
Order By: Relevance
“…Stradivari's own letter indicated the exposure of instruments to sunlight (1), and further light exposures were inevitable over the course of three centuries. Oxidation may cause lignin demethoxylation (15) and the formation of quinone groups (7,16), resulting in peak broadening due to increased structural heterogeneity, as well as decreased CP signals due to hydrogen loss nearby. In modern wood, the carbonyl peak at 173 ppm is mainly associated with the acetyl groups in hemicellulose.…”
Section: Resultsmentioning
confidence: 99%
“…Stradivari's own letter indicated the exposure of instruments to sunlight (1), and further light exposures were inevitable over the course of three centuries. Oxidation may cause lignin demethoxylation (15) and the formation of quinone groups (7,16), resulting in peak broadening due to increased structural heterogeneity, as well as decreased CP signals due to hydrogen loss nearby. In modern wood, the carbonyl peak at 173 ppm is mainly associated with the acetyl groups in hemicellulose.…”
Section: Resultsmentioning
confidence: 99%
“…Strictly speaking, however, the claim of accelerated ageing has little basis in reality, because the ageing of wood involves many different chemical reactions following different reaction kinetics. Chédev-ille and co-researchers have confirmed that ultraviolet resonance Raman spectra of artificially aged wood were dissimilar to those of naturally aged wood when the wood was heated to 160 • C or above [33]. This suggests that the properties of naturally aged wood are not easily reproduced by the hydrothermal treatment of new wood.…”
Section: Artificial Ageing Of Woodmentioning
confidence: 98%
“…The inner dimensions of the autoclave were 200 mm 9 150 mm 9 80 mm. According to Chédeville et al (2012), the chemical reactions induced by heating at 150°C or higher are qualitatively different from those at 130°C or lower. Therefore, 120°C was employed as the treatment temperature because the final goal was the reproduction of naturally aged wood.…”
Section: Hydrothermal Treatmentmentioning
confidence: 99%